Examining Behavioral Intention and Use Behavior in Online Learning Among Students of Vocal Language and Art College in Chengdu, China - Shuqin, Xiang; Feng, Deping; Ming, Yang (Scholar: Human Sciences, 2025)
Purpose: This study aims to explore the factors affecting students' behavioral intention and use behavior in the context of online learning at a private university specializing in vocal language and art college in Chengdu, China. The conceptual framework incorporated perceived ease of use, usefulness, attitude toward use, social influence, trust, behavioral intention, and use behavior. Research design, data, and methodology: . The researcher employed a quantitative survey methodology to distribute questionnaires among the students at the targeted college. 472 valid data were assessed. Item-Objective Congruence (IOC) was evaluated for content validity. 40 students were involved in the pilot test for Cronbach’s Alpha reliability test. Confirmatory Factor Analysis (CFA) was conducted to ensure the construct validity of the relationship between the collected data and the proposed conceptual framework. Furthermore, Structural Equation Modeling (SEM) was utilized to assess the significant factors affecting the variables related to behavioral intention. Results: The results of the study confirmed all seven hypotheses. Notably, the results of this study testing the hypotheses indicate that behavioral intention significantly impacts use behavior. Conclusions: Future improvements for online learning platforms should focus on introducing interactive tutorials and guides, incorporating specialized tools tailored to creative fields, and bolstering feedback mechanisms.